Enhanced degradation of phenol in floating treatment wetlands by plant-bacterial synergism. Issue 7 (7th June 2018) - Saleem, Hamna; Rehman, Khadeeja; Arslan, Muhammad; Afzal, Muhammad
ABSTRACT: Phenol is a commonly found organic pollutant in industrial wastewaters. Its ecotoxicological significance is well known and, therefore, the compound is often required to be removed prior to discharge. In this study, plant-bacterial synergism was established in floating treatment wetlands (FTWs) in an attempt to maximize the removal of phenol from contaminated water. A common wetland plant, Typha domingensis, was vegetated on a floating mat and augmented with three phenol-degrading bacterial strains, Acinetobacter lwofii ACRH76, Bacillus cereus LORH97, and Pseudomonas sp. LCRH90, to develop FTWs for the remediation of water contaminated with phenol. All of the strains are known to have phenol-reducing properties, and grow well in FTWs. Results showed that T. domingensis was able to remove a small amount of phenol from the contaminated water; however, bacterial augmentation enhanced the removal potential significantly, i.e., 0.146 g/m 2 /day vs. 0.166 g/m 2 /day, respectively. Plant biomass also increased in the presence of bacterial consortia; and inoculated bacteria displayed successful colonization/survival in the rhizosphere, root interior and shoot interior of the plant. Similarly, highest reduction in chemical oxygen demand (COD), biochemical oxygen demand (BOD5 ), and total organic carbon (TOC) was achieved by the combined application of plants and bacteria. The study demonstrates that the plant-bacterial synergism in a FTW may be a more effective approach for the remediation of phenol-contaminated water.